2012
DOI: 10.1111/j.1365-2702.2012.04180.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and spiritual caring: nurses’ perspectives and practice in palliative and acute care environments

Abstract: The development of nurses' spiritual perspective early in their preparation for practice, and the articulation and documentation of spiritual caring may enhance their spiritual caring practice. Further research on barriers to spiritual caring in acute care nursing environments is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
84
1
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 40 publications
(61 reference statements)
12
84
1
8
Order By: Relevance
“…However, the need for further education for nurses and other healthcare professionals in relation to the best methods of delivering spiritual care is evident (Jafari et al 2014a;Rassool 2000). In both Middle Eastern and Western contexts, factors such as workload, lack of time, lack of knowledge, and insufficient resources, most likely contribute to this issue of spiritual care delivery in practice (Balboni et al 2014;Baldacchino 2008;Cadge et al 2009;O'Brien 2007;Ronaldson et al 2012;Wong and Yau 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the need for further education for nurses and other healthcare professionals in relation to the best methods of delivering spiritual care is evident (Jafari et al 2014a;Rassool 2000). In both Middle Eastern and Western contexts, factors such as workload, lack of time, lack of knowledge, and insufficient resources, most likely contribute to this issue of spiritual care delivery in practice (Balboni et al 2014;Baldacchino 2008;Cadge et al 2009;O'Brien 2007;Ronaldson et al 2012;Wong and Yau 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was assessed based on a question from a national study of physicians: 16 “Please indicate the degree to which you agree with the following statement: My religious/spiritual beliefs influence my practice of medicine,” and was measured on a five-point scale from “strongly agree” to “strongly disagree” and within analyses dichotomized to “strongly agree/somewhat agree” vs. “neutral/somewhat disagree/strongly disagree.” …”
Section: Figmentioning
confidence: 99%
“…Spiritual care practices may differ, considering the environment in which health care is provided 18 . This care is not perceived as a priority in emergency care due to the very essence of the service, which aims to revert or stabilize the clinical picture of the patient.…”
mentioning
confidence: 99%
“…It is noteworthy that nurses are more cited than other professionals in studies that discuss spirituality in coping with diseases 14,17,18 . It is also observed that Leininger's cross-cultural nursing theory is approached 16 as a useful tool to be developed by other professionals in the field, considering cultural diversity and including spiritual aspects in the health and disease process when desired by the patient or family member.…”
mentioning
confidence: 99%